Impact of Including Readmissions for Qualifying Events in the Patient Safety Indicators - Davies, Sheryl M. (Am J Med Qual, 2014)
The Agency for Healthcare Research and Quality (AHRQ) Patient Safety Indicators (PSI) do not capture complications arising after discharge. We sought to quantify the bias due to omission of readmissions for PSI-qualifying conditions. Using 2000–2009 California Office of Statewide Health Planning and Development Patient Discharge Data we examined the change in PSI rates when including readmissions in the numerator, hospitals performing in the extreme deciles and longitudinal performance. Including 7-day readmissions resulted in a 0.3% – 8.9% increase in average hospital PSI rates. Hospital PSI rates with and without PSI-qualifying 30-day readmissions were highly correlated for point estimates and within-hospital longitudinal change. Most hospitals remained in the same relative performance decile. Longer length of stay, public payer, and discharge to skilled nursing facilities were associated with a higher risk of readmission for a PSI-qualifying event. Failure to include readmissions in calculating the PSIs is unlikely to lead to erroneous conclusions.